The opposing forces of shear flow and sphingosine-1-phosphate control marginal zone B cell shuttling - Kerry Tedford (Nature Portfolio, 2017)
Marginal zone B (MZB) cells shuttle between the marginal zone and lymphoid follicle to capture and present peripheral blood antigens. Here the authors show that shear force, such as blood flow from the sinus around the follicle, is a directional cue that induces MZB migration on ICAM-1, and that S1P signaling inhibits this directional migration.